Analysis of the customer experience in digital social networks: Restaurants in the city of Ibagué-Colombia - Andrade, Luis Enrique Caballero; Guzman, Rafael Alfonso Toro (International Journal of Innovative Research and Scientific Studies, 2025)
This study analyzes the customer experience in digital social networks within the restaurant sector in Ibagué, Colombia, assessing how engagement and implicit attitudes shape consumer perceptions. Using a mixed-methods approach, the research selected top-rated restaurants on TripAdvisor and collected engagement metrics from their Instagram and Facebook accounts. Additionally, an Implicit Association Test (IAT) was applied to measure unconscious consumer attitudes toward visual content. Findings indicate that engagement does not always correlate with follower count; restaurants with fewer but highly interactive followers demonstrated stronger engagement. The IAT results showed mild but significant associations between implicit attitudes and engagement, suggesting that consumer perceptions are influenced by subconscious responses to digital content. The study highlights the role of digital engagement in shaping customer experiences and emphasizes the need for strategic content creation to foster meaningful interactions. These insights can help restaurant owners and marketers optimize their social media strategies by prioritizing visually compelling content and encouraging active consumer participation to enhance digital engagement and strengthen brand perception.